The Integration of Artificial Intelligence in Advanced Management Accounting, Evidence from Albania and Implications for International Education Standards in Accounting - Ramaj, Brisejda Zenuni (European Journal of Social Science Education and Research, 2025)
Artificial Intelligence (AI) is increasingly redefining management accounting, not only by automating routine tasks and enhancing decision-making but also by influencing professional competencies, organizational learning, and workforce development. This study examines AI adoption in Albanian organizations, investigating how organizational experience, employee position, and AI-supported budgeting systems affect financial decision-making and professional skill development. A total of 155 managers, accountants, and operational staff completed a structured online questionnaire. Reliability and validity were confirmed through Cronbach’s Alpha and Exploratory Factor Analysis. Regression analyses show that more experienced organizations adopt AI more extensively, managerial staff use AI tools more than operational employees, and AI-based budgeting efficiency significantly enhances decision-making quality. Importantly, professional competence moderates these effects, highlighting the critical role of human expertise. The findings emphasize the educational and social implications of AI adoption, suggesting that workforce training, curriculum alignment, and continuous professional development are essential for maximizing AI’s benefits in accounting.
Keywords: Artificial Intelligence; Management Accounting; Accounting Education, Financial Decision-Making, AI Adoption, Professional Development, Higher Education, Social Impact